(untitled) (Хабаршы. Психология және социология сериясы, 2023)
This study aims to analyze the socio-demographic profile of internal migrants residing in Almaty. The main goal of the study is to identify socio-demographic characteristics of internal migrants, such as gender, education level, age group, nationality and marital status. To achieve this goal, the data provided by the Bureau of National Statistics of the Agency for Planning and Reforms of the Republic of Kazakhstan (BNS APR RK) from 2017 to 2022 and data from the scientific project IRN AR 09058370 "Social integration of internal migrants in the local community of large cities: social networks, social capital and urban space development" under the leadership of S.S. Serikzhanova were used. The study applied proportional analysis conducted in Statistical Analysis System (SAS), using a frequency table and a summary procedure. The analysis involved examining the distribution of categorical variables to determine the relative frequencies or proportions of each category in the dataset. The significant finding of the analysis indicates that a substantial majority of internal migrants are female who belong to the Kazakh nationality and are of working age. Furthermore, it reveals that most of these female migrants have a higher education level and are married. The predominant trend among these female migrants is their origin from rural areas. The study’s findings hold practical significance for future research in the field of internal migration, including its dynamics, trends, and the social integration of internal migrants into urban society. Additionally, the results provide valuable insights into the social processes within the city, such as the spatial and socio-demographic transformations. Keywords: internal migration, Kazakhstan, sociodemographic portrait, urban society transformation.